The history of the Kazakh written signs - Akhmediyeva K, Ybyraimzhanov К, Bekish A, Mailybaeva G, Shengelbayeva S (Opción, 1970)
This article discusses the primary education systems on Kazakhland and the history of written signs, and alphabets based on systemdescriptions via analysis from a philosophical, historical, sociopoliticaland pedagogical-psychological point of view. As a result, Activitiescarried out in Kazakhstan to translate the Kazakh script into the Latinalphabet, were ill-conceived, they did not solve the problem of theKazakh alphabet, and it was evident from the experience. Inconclusion, there was a reform of the Kazakh script in the system oforganization of the educational process in primary school.